Towards zero-energy architecture : new solar design - Guzowski, Mary (Laurence King, 2012)
This book explores the theories, practices and principles of new approaches to solar architecture that foster both design excellence and low-energy use. In response to the challenges of global warming and climate change, design and technology enable architects to achieve greater performance standards while at the same time developing an environmental aesthetic. The book showcases ten award-winning buildings to illustrate the aesthetic and technological design integration of solar response in contemporary zero-energy and low-energy architecture. For each project there is a detailed examination of the local climate, the design and construction, and the technology used to reduce energy use. "Towards Zero-energy Architecture" is a much-needed call for the design professions to redefine architecture to help solve ecological problems.